1999
DOI: 10.1046/j.1365-2672.1999.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods for DNA extraction from various soils: a comparison

Abstract: Seven methods for bacterial DNA extraction and purification from soil samples were compared. Holben’s direct lysis method recovered significantly greater amounts of DNA than the other methods tested, while CsCl‐ethidium bromide density gradient ultracentrifugation was better than gel filtration at removing humic acid from crude DNA isolated from soil. When both these methods were combined, 5·94 μg of DNA (A260/280 ratio around 1·754) was yielded g−1 oven‐dried sandstone shale alluvial soil; similarly satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 19 publications
(24 reference statements)
1
28
1
Order By: Relevance
“…Compared to these two direct extraction methods, the indirect extraction method of Jacobsen and Rasmussen [28] based on centrifugation recovery of cell fraction before lysis and CsCl DNA purification, gave the lowest DNA yield but showed the highest DNA purity with a low degree of DNA shearing. Tien et al [65] reported that the direct lysis methods produced similarly DNA yield at least a 10-fold greater than the indirect extraction methods.…”
Section: Comparative Evaluation Of Direct and Indirect Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to these two direct extraction methods, the indirect extraction method of Jacobsen and Rasmussen [28] based on centrifugation recovery of cell fraction before lysis and CsCl DNA purification, gave the lowest DNA yield but showed the highest DNA purity with a low degree of DNA shearing. Tien et al [65] reported that the direct lysis methods produced similarly DNA yield at least a 10-fold greater than the indirect extraction methods.…”
Section: Comparative Evaluation Of Direct and Indirect Methodsmentioning
confidence: 99%
“…3. Nucleic acid extraction should be performed as soon as possible after sample collection since storing samples at 4°C for several weeks can result in the degradation of the large molecular-weight DNA fraction [65].…”
Section: Toward a Universal Lysis Extraction Method?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several environmental DNA isolation and purification strategies have previously been investigated with variable rates of success (Cullen and Hirsch 1998;Miller et al 1999;Tien et al 1999). In this study, extraction techniques that are compatible with sediments obtained from multiple depths were evaluated based on DNA yield, ability to detect microbial community members by PCR-DGGE, and ability to determine the relationships between the microbial community and environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent dyes have difficulty penetrating particular types of microorganisms in-situ (e.g., lichens (see Weinstein et al, submitted manuscript, 2007)); culturing has been known to underestimate microbial abundance by 1 to 2 orders of magnitude; a vast majority of microbial diversity has proven refractory to cultivation; and the efficiency of DNA extraction varies widely [Amman et al, 1995;Hartmann et al, 1997;Miller et al, 1999;Tien et al, 1999 Table 2). Geologic map units include m (mountain-forming materials), d (dissected materials, d1, d2 and d3), s (scalloped terrain) and f (fan materials).…”
Section: Habitats and Microbiologymentioning
confidence: 99%